2021
DOI: 10.1039/d1gc01850g
|View full text |Cite
|
Sign up to set email alerts
|

Radical induced disproportionation of alcohols assisted by iodide under acidic conditions

Abstract: The disproportionation of alcohols without additional reductant and oxidant to simultaneously form alkanes and aldehydes/ketones represents an atom-economic transformation, which has great potential for organic synthesis. However, only limited methodologies...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The addition of different amounts of water led to an increase in the yield of 5‐MF (Scheme 16a) [39] . Under optimized conditions, 5‐MF and DFF were obtained in a 49 % yield each by using NaI and sulfuric acid (H 2 SO 4 ) in tetrahydrofuran (THF) under N 2 atmosphere at 180 °C [44] . The application of the NaI/H 2 SO 4 deoxygenation process to a small collection of alcohols showed that substituents had no significant effect on the yields and ratios of disproportionation products (Scheme 16b).…”
Section: Reduction Of C−o Bondsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of different amounts of water led to an increase in the yield of 5‐MF (Scheme 16a) [39] . Under optimized conditions, 5‐MF and DFF were obtained in a 49 % yield each by using NaI and sulfuric acid (H 2 SO 4 ) in tetrahydrofuran (THF) under N 2 atmosphere at 180 °C [44] . The application of the NaI/H 2 SO 4 deoxygenation process to a small collection of alcohols showed that substituents had no significant effect on the yields and ratios of disproportionation products (Scheme 16b).…”
Section: Reduction Of C−o Bondsmentioning
confidence: 99%
“…[43] In addition to Yang's research on iodide-mediated processing of biomass derivatives to added-value chemicals, a disproportionation of alcohols catalyzed by iodide was also described. [44] Previously, Yang found that when 5-hydroxymeth- ylfurfural was exposed to NaI, a Brønsted acid, and H 2 under anhydrous conditions, it generated 5-methylfurfural (5-MF) and diformylfurfural (DFF). The addition of different amounts of water led to an increase in the yield of 5-MF (Scheme 16a).…”
Section: Reduction Of Cà O Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, apart from the desired product benzaldehyde (4 a) was generated, benzoic acid (5 a) was also presented as an accompanied product with the yields of 41%, which was detrimental to the selectivity of reaction (Table 2, Entry 1). Inspired by the previous studies on selective dehydrogenation of primary alcohols, [13] various iodides were used as additives to suppress the formation of 5 a.…”
Section: Resultsmentioning
confidence: 99%
“…The one pathway was direct cleavage of the OÀ H bond via transition state TS 12 and TS 33 with the generation of the product 2 a and 4 a, the energy barriers for such process was calculated as 44.23 and 43.26 kcal/ mol, respectively. The other pathway was that the 1,3-H shift process was first occurred within the intermediate 1 a-OOH (formed by combination of 1 a * and HOO * ) and 3 a-OO À (formed ), thereafter the final product 2 a and 4 a was produced by the cleavage of CÀ O bond within the intermediate via transition state TS 13 and TS 34 . The calculation showed that the energy barrier of the 1,3-H shift process within the intermediate 1 a-OOH and 3 a-OO À were 1.63 and 4.48 kcal/ mol, respectively, besides, the cleavage of CÀ O bond was proved to be an energy barrierless process by relax scanning calculation, which indicated that the latter pathway was more preferable for the reaction of 1 a * and 3 a * .…”
Section: Resultsmentioning
confidence: 99%